Study on Long-Term Dynamic Mechanical Properties and Degradation Law of Sandstone under Freeze-Thaw Cycle - Qingsong Pu; Junhong Huang; Fuling Zeng; Yi Luo; Xinping Li; Jixue Zhou; Shilong Zheng (Shock and Vibration)
This study is based on the tunnel-face slope engineering of Dongfeng tunnel in Shanxi section of China’s Shuozhou-Huanghua Railway. The sandstone specimens in the perennial freeze-thaw zone of the slope were collected to carry out freeze-thaw cycle static physical mechanics test and split Hopkinson pressure bar (SHPB) dynamic mechanical test. Thus, the damage process of sandstone under freeze-thaw cycle and impact load is studied. Also, the dynamic compressive strength and dynamic elastic modulus of sandstone are analysed under different loading strain rates and freeze-thaw cycle based on LS-DYNA, a dynamic finite element program. The results showed that the dynamic compressive strength of sandstone subjected to multiple freeze-thaw cycles under 0.04 MPa air pressure has a greater damage ratio than that under 0.055 MPa and 0.07 MPa air pressure, which was more likely to cause damage to slope sandstone than in actual engineering; the dynamic compressive strength and elastic modulus of sandstone decrease greatly within a certain range of freeze-thaw cycles and loading strain rate, leading to significant deterioration. When the freeze-thaw cycle exceeded 200 times and the strain rate was greater than 200 s−1, the physical and mechanical properties of sandstone gradually tended to be stable.